STRATEGI COPING PADA PENDERITA STROKE - Hasan, Nur (JURNAL TALENTA PSIKOLOGI, 2013)
There many symptoms arisd got a stroke attack, such as half body paralysis, mouth askew, hard talking, difficulty speaking (no to reveal what he wants), can’t read or written, cleverness, forgetfulness, impaired vision, less hearing, feels more sensitive, sexuality disorders, urinary incontinence, and cannot do the toiletries by himselves.As psychologically, people with stroke have achange and limitations in moving, communicating, and thinking that is really going to disrupt the function of the role of patient. Social support will greatly assist individuals to make adjustments or positive coping behaviors and personality development and can function as a barrier to prevent the effect of psychological disorders.